FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Muthmainnah; Ismail Noy; Ernawaty Usman; Nur Handayani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
An auditor is an attractive choice for accounting graduates in Indonesia. This profession is useful in auditing the financial statements. An auditor must have high integrity to detect fraud and risk. In addition, the mental attitude and professionalism are highly to maintain professionalism and liquidity. This study is a survey-based quantitative research that seeks to look at how competence, auditor independence, time pressure, and experience affect auditors' ability to find fraud. The effect of these factors is looked at through the lens of professional skepticism, and the research is focused on a representative financial audit body in Papua Province. The research design uses probability with purposive sampling techniques and the sample unit in Inspection Officers (BPK) Papua Province. The institution has a total of 88 auditors. The research data is sourced from primary data collected using questionnaire instruments. The moderation analysis in this study uses the Partial Least Square (PLS) approach. The results of the study found that the competence, independence and experience of auditors have a positive and significant influence on the ability of auditors to detect fraud at the Papua Province Financial Audit Agency (BPK).